The mathematical and pedagogical content knowledge that Namibian senior primary teachers draw on to develop their learners' computational estimation - Shigwedha, Emilia Ndilimeke (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
Computational estimation is important in the development of learners' number sense. It is through the process of finding an approximate (but satisfactory) that learners can check the reasonableness of their answers to calculations, develop an understanding of place value and by implication the four number operations. It is the role of teachers to develop the computational estimation skills of learners. To do this, teachers need to have a sound knowledge of computational estimation, its value and how to teach it. This study thus seeks to explore and understand Namibian senior primary teachers' mathematical and pedagogical content knowledge to develop their learners' computation estimation knowledge. The research is guided by the following question: What mathematical and pedagogical content knowledge do senior primary mathematics teachers draw on to develop their learners' computational estimation skills? The research is a qualitative interpretivist case study. Eight senior primary teachers of Mathematics from the Ohangwena region in Namibia participated in the study. Data was generated through questionnaires, a focus group interview and lesson observations. The Mathematics Knowledge for Teaching (Ball et al., 2008) and the Knowledge Quartet (Rowland, 2005) frameworks were used as both analytic and explanatory tools for the study. Key findings from the research are that teachers have knowledge of and use a variety of strategies for estimation, however, they only use the 'rounding off' strategy when teaching learners computational estimation. The teachers appear to teach computational estimation by first focusing on place value before moving on to 'rounding off' to the nearest 10s, 100s, 1000s and so forth. My research recommends that the National Institute of Educational Development together with the Ministry of Education, Art and Culture in Namibia, provide teachers with professional development opportunities on how to develop learners' computational estimation. Such professional development will further develop teachers' mathematical and pedagogical content knowledge. Furthermore, the Namibian syllabus should include a variety of strategies for computational estimation.
Keywords: Mathematics-- Study and teaching (Primary)-- Namibia; Approximation theory; Pedagogical content knowledge; Mathematics teachers In-service training-- Namibia; Mathematics-- Namibia Outlines, syllabi, etc